Factors associated with suicidal risk among UCSI university students / Nur Aqilah Zainordin ... [et al.] - Zainordin, Nur Aqilah; Md Zaki, Noor Zira Azlin; Angky, Aldrin Alvian; Fransiska, Bella; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2022)
Mental health is something that humans should be concerned about, and without exception, the UCSI students. Mental health issues can cause students to experience a higher risk of depression, anxiety, and stress which somehow will affect the students' academic performance, their relationships with family and friends, and their future. Eventually, it could stimulate suicidal thoughts among students and influence them to commit suicide. Therefore, this research is conducted to determine the risk of depression, stress, and anxiety affecting UCSI students that could influence suicidal thoughts and commit suicide. This research is intended for all the faculties at UCSI University. There were questionnaires distributed online and offline for data collection purposes. The data were analysed using both DASS 21 (Depression, Anxiety, and Stress Scale) and a 5-point Likert scale for both the questionnaires using IBM SPSS Version 20. The findings from the research showed that depression, anxiety and stress have shown a relationship with suicide. The recommendations for this study are to improve the awareness related to suicide, particularly among university students. Society should be aware related to depression, anxiety and stress that can impact to commit suicide among university students.